The first months of the activities of the courts of peace in the Court of Appeal in the Poznan circuit in the light of the court files from the Court of Appeal in Poznan - Paciorkowski, Szymon Paciorkowski (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2015)
The aim of the paper is to present the activities of the courts of peace in the Court of Appeal in the Poznan circuit in the Polish Second Republic in the first months of their existence in 1920. The courts of peace were established in the former Prussian partition by the Polish authorities because of the shortage of Polish legal professionals. Justices of the peace were appointed from the local citizenry and most of them had no formal legal education. The article, which is primarily based on the study of court files from the Court of Appeal in Poznan, deals with selected problems concerning the implementation of the courts of peace, like issues connected with the appointment of new justices and the financial compensation for their activities at court.